Persentase Tutupan Karang Di Perairan Teluk Akle Kecamatan Semau Selatan Kabupaten Kupang Nusa Tenggara Timur - Alexander Leonidas Kangkan; Ade Yulita Hesti Lukas; Sevanster Lakapu; Kiik Gretty Sine (Fakultas Kelautan dan Perikanan Universitas Udayana, 2023)
Akle Bay is one of marine aquaculture area in Semau island and it has coral reef potention. The coverage percentage of coral reef in the ocean might be decline by human activities and also by nature itself. The aimed of this research was analyzed to know the percentage of coral reef coverage in Akle Bay, South Semau District. This study conducted in Akle Bay, South Semau District on May 18, 2023st . Underwater Photo Transect (UPT) was used to take a sample in five meter depth at two different sites in Akle Bay waters. Data was analyzed by software CPCe 4.1. Result showed the highest benthic coverage percentage is soft coral. There were eleven genus of hard coral was found and its dominated by Porites genera. The percentage of hard coral coverage in S1 was 9.14%, while in S2 was 6.11% and was categorized in worst condition. The decline of coral reef coverage percentage in this area was expeted due to of human activities such as coral removal, the usage of anchor and the destructive fishing gear like a bomb, and also a sedimentation. According to the lifeform, covarage percentage of hard coral was dominated by coral branching. The average of current velocity in Akle Bay was 0,417 m/s with the range of waves was 0.1 to 0.5 meters. Conclusion of this research is the percentage of coral coverage in Akle Bay is worst. It was becacuse of human activities and sedimentation.